CULTURE DIFFERENCES AFFECT PERFORMANCE AND ASSESSMENT ACCEPTANCE OF CHINESE STUDENT (Jurnal Manajemen Perhotelan, 2012)
Stenden University is an international hospitality management university in Leeuwarden, Netherlands which the major Asian student is from China. Thus, cultural differences might stimulate an influence towards Chinese students’ daily performance and assessment acceptance. Throughout in-depth interview with the Chinese students, it reveals that there are some culture barriers for Chinese student during their practice. These affect in their basic skill, relationship, communication, and language. These matters also affect Chinese student’s assessment acceptance that they tend to accept, even though they do not agreeing with their assessment.